PELATIHAN PEMBUATAN LAYOUT PCB DENGAN DIP TRACE DAN DRY FILM PHOTORESIST BAGI SMK MUHAMMADIYAH 2 SALAM MAGELANG - Denny Dermawan (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2018)
The desire of students of SMK Muhammadiyah 2 Salam Magelang to be able to make a printed circuit board is something that is very important to be welcomed and followed up wisely so that the desire of the students is not just a wishful dream but will be a reality. This activity is meant to be an effort not only to overcome difficulties at certain times (short-term activities), but is expected to be sustainable for the future (longer term). Looking at the fact, of course, should be strived to realize the handling of the problem at least for the near term. For that required activities that are practical and immediate benefits can be taken as the activity can be a short course or short training. To solve the problem, it is realized by holding a short course / training course on PCB Layout Creation with DIP TRACE and Dry Film Photoresist technology followed by etching process, drilling and installation of components that will be useful for students who want to do the main final work related with the manufacture of tools / hardware. Keywords: Making PCB, DIP TRACE, Dry Photoresist film